Acceleration of bone formation during fracture healing by poly(pro–hyp–gly)10 and basic fibroblast growth factor containing polycystic kidney disease and collagen‐binding domains from Clostridium histolyticum collagenase. Issue 6 (16th February 2016) - Sekiguchi, Hiroyuki; Uchida, Kentaro; Inoue, Gen; Matsushita, Osamu; Saito, Wataru; Aikawa, Jun; Tanaka, Keisuke; Fujimaki, Hisako; Miyagi, Masayuki; Takaso, Masashi
Abstract: Growth factor delivered in combination with animal‐derived collagen materials has been used to accelerate bone fracture healing in human patients. However, the introduction of bovine proteins into humans carries the risk of zoonotic and immunologic complications. Here, we developed a collagen‐like polypeptide‐based bone formation system consisting of poly(Pro‐Hyp‐Gly)10, which mimics the triple helical conformation of collagen, and basic fibroblast growth factor (bFGF) fused to the polycystic kidney disease (PKD) domain and collagen‐binding domain (CBD) of Clostridium histolyticum collagenase. Circular dichroism spectral analysis showed that when pepsin‐soluble bovine type I collagen was treated at 50°C, a positive signal corresponding to the collagen triple helix at 220 nm was not detected. In contrast, poly(Pro‐Hyp‐Gly)10 retained the 220‐nm positive peak, even when treated at 80°C. The combination of the collagen binding‐bFGF fusion protein (bFGF‐PKD‐CBD) with poly(Pro‐Hyp‐Gly)10 induced greater bone formation compared to bFGF alone in mice bone fracture models. Taken together, these properties suggest that the bFGF‐PKD‐CBD/poly(Pro‐Hyp‐Gly)10 composite is a promising material for bone repair in the clinical setting. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1372–1378, 2016.